KEABSAHAN KONTRAK TANDA TANGAN ELEKTRONIK DALAM PERJANJIAN PENDANAAN P2P LENDING - Catherine Carisa Khovin; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2022)
Peer-to-Peer Lending is now familiar to the public. Its ease of investing makes people not hesitate to try to invest with this service. In addition, the small risk of loss is also the reason many people try to invest through Peer-to-Peer Lending services. The increasing number of smartphone users makes people who are trying to invest in these services increase because the interest is also in Peer-to-Peer Lending Services more and more. The problem discussed in this study is how the legal force of electronic signatures in funding agreements (P2P Lending) in courts in the event of disputes in courts according to the Civil Procedure Law. The research was conducted using the literature study method with the statute approach method. Civil procedural law does not specifically regulate electronic evidence. Meanwhile, along with the development of technology, legal products are also updated or formed new ones. Although civil procedural law does not directly regulate electronic evidence, the expansion of such evidence is regulated in the Electronic Information and Transactions Law.